A review of exercise pulmonary hypertension in systemic sclerosis. Issue 3 (October 2019) - Shaikh, Faisal; Anklesaria, Zafia; Shagroni, Tasneam; Saggar, Rajeev; Gargani, Luna; Bossone, Eduardo; Ryan, Michael; Channick, Richard; Saggar, Rajan
In general, pulmonary vascular disease has important negative prognostic implications, regardless of the associated condition or underlying mechanism. In this regard, systemic sclerosis is of particular interest as it is the most common connective tissue disease associated with pulmonary hypertension, and a well-recognized at-risk population. In the setting of systemic sclerosis and unexplained dyspnea, the concept of using exercise to probe for underlying pulmonary vascular disease has acquired significant interest. In theory, a diagnosis of systemic sclerosis–associated exercise pulmonary hypertension may allow for earlier therapeutic intervention and a favorable alteration in the natural history of the pulmonary vascular disease. In the context of underlying systemic sclerosis, the purpose of this article is to provide a comprehensive review of the evolving definition of exercise pulmonary hypertension, the current role and methodologies for non-invasive and invasive exercise testing, and the importance of the right ventricle.